Pelayanan Pastoral Kedukaan Akibat Kematian Yang Mendadak - Amperiyana Nguru (TE DEUM (Jurnal Teologi dan Pengembangan Pelayanan), 2019)
This research is intended to give attention to people who are grieving because of sudden death. Separation because of death is a "very strenuous" situation for someone because it can cause stress and depression with impacts on psychological well-being, socio-culture, and spirituality. In addition, many people who mourn are not ready to face the separation. Taking the aforementioned things into consideration, the author wants to conduct research and provide help through healing pastoral care. What is meant by healing is to make a grieving person "rise up" from his prolonged grief. Furthermore, it is expected that the mourners can move on in living the future. Sampling was carried out on 5 cases of sudden death at GPIB Sejahtera Bandung. The pastoral care that has been carried out by GPIB Sejahtera Bandung as a whole has not been ideal and has not touched the grief experienced by its members, because the pastoral care of grief has only been served in the form of consolation services carried out before the funeral, deliverance and funeral services, and thanksgiving worship that was held after the funeral. As a result there is nothing that helps the grieving people to be able to rise from their prolonged grief. Relevant pastoral care for people who grieve at GPIB Jemaat Sejahtera Bandung is healing pastoral care. Healing pastoral care is expected to be able to resolve the damage experienced by someone by restoring the person towards wholeness and guiding him/her to reach a better state than the original condition.